2003
DOI: 10.2135/cropsci2003.1960
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Fusarium Head Blight in Four Populations of Barley

Abstract: Fusarium Head Blight (FHB), caused by Fusarium graminearum Schwabe [(teleomorph Giberella Zeae (Schwein.)], has been a major disease problem of barley (Hordeum vulgare L.) in the U.S. Midwest since 1993. It can make a potentially profitable barley crop unusable for malting, and substantially reduce its value as a feed grain. The main cause of economic loss in malting barley is the presence of deoxynivalenol (DON) or vomitoxin, a mycotoxin produced by the fungus. The objective of this research was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In our field analyses, we observed that the interactions of the genotype with the environment determine, to the same extent, the phenotypic variation of symptoms on the spike, the DON content and the reduction of grain filling. Heritability of resistance against FG infection is therefore lower than that in wheat, confirming the findings of other authors (Bai et al 2000;Urrea et al 2002;Capettini et al 2003). Consequently, in practical breeding, the expected genetic of FHB resistance is rather weak.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our field analyses, we observed that the interactions of the genotype with the environment determine, to the same extent, the phenotypic variation of symptoms on the spike, the DON content and the reduction of grain filling. Heritability of resistance against FG infection is therefore lower than that in wheat, confirming the findings of other authors (Bai et al 2000;Urrea et al 2002;Capettini et al 2003). Consequently, in practical breeding, the expected genetic of FHB resistance is rather weak.…”
Section: Discussionsupporting
confidence: 86%
“…Strong interactions between the genotypes and the environments indicate a weak stability of barley resistances traits of spike and grains previously mentioned in genetic studies (Capettini et al 2003;De la Pena et al 1999). In our field analyses, we observed that the interactions of the genotype with the environment determine, to the same extent, the phenotypic variation of symptoms on the spike, the DON content and the reduction of grain filling.…”
Section: Discussionmentioning
confidence: 77%
“…These results proved the high environmental effects in the determination of resistant germplasm. Different locations and years of testing are necessary to identify resistant genotypes, and the conditions simulated in the nurseries are essential to increase the heritability of the resistance (Capettini et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Use of barley grain contaminated by DON can result in processing problems, including beer off-flavors and gushing, as well as the reality/perception that DON may be a carcinogen (Schwarz et al 2003;Steffenson et al 2003). Host resistance is an important component in FHB management system and has the recognized advantage of being cost-effective and environmentally friendly, although it is hard to achieve due to the lack of known immunity and quantitative inheritance (Capettini et al 2003). Similar to wheat, Type I (resistance to initial infection) and Type II (resistance to fungal spread within plant tissue) resistance have also been reported in barley, although the former is regarded to be more important (McCallum and Tekauz 2002;Steffenson et al 2003;Geddes et al 2008).…”
mentioning
confidence: 99%
“…Resistance to accumulation of DON would be very desirable, particularly in barley, but to date there is little evidence for it. Type II resistance has been identified in barley (Zhu et al, 1999), but its value is not clear (Capettini, 1999).…”
Section: Nature Of the Inheritance Of Resistance To Fhbmentioning
confidence: 99%